2018
DOI: 10.1021/acssuschemeng.8b01842
|View full text |Cite
|
Sign up to set email alerts
|

Depolymerization of Waste Plastics to Monomers and Chemicals Using a Hydrosilylation Strategy Facilitated by Brookhart’s Iridium(III) Catalyst

Abstract: Plastic waste management is a major concern. While the societal demand for sustainability is growing, landfilling and incineration of waste plastics remain the norm and methods able to efficiently recycle these materials are desirable. Herein, we report the depolymerization, under mild conditions, of oxygenated plastics in the presence of hydrosilanes with the cationic pincer complex [Ir(PCP)H(THF)][B(C6F5)4] (PCP = 1,3-(tBu2P)2C6H3)) as catalyst. The iridium catalyst, with a low loading (0.3-1 mol%), proves s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 41 publications
0
111
0
Order By: Relevance
“…Compared to other waste management strategies such as incineration and biodegradation, chemical recycling offers the greatest value with potential to reduce the cost of PLA and increase market uptake . Previous examples of PLA recycling processes include hydrolysis, alcoholysis, hydrogenation and hydrosilylation …”
Section: Methodsmentioning
confidence: 99%
“…Compared to other waste management strategies such as incineration and biodegradation, chemical recycling offers the greatest value with potential to reduce the cost of PLA and increase market uptake . Previous examples of PLA recycling processes include hydrolysis, alcoholysis, hydrogenation and hydrosilylation …”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29] A number of different PLA transesterification methods have been reported in the literature. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] DuPont possess a patent for PLA degradation in the presence of H 2 SO 4 , achieving high conversion (69-87%) to various lactate esters (R = Me, Et and n Bu) within 2 h between 150-190°C. 30 Coszach et al 17 demonstrated the hydrolysis of PLA to lactic acid, observing enhanced PLA dissolution and polymer separation with lactate esters as the solvent of choice.…”
Section: Introductionmentioning
confidence: 99%
“…Catalysts based on rare metals, including iridium and ruthenium, have also been reported for hydrogenation and hydrosilylation processes, but are unattractive options to industry due to a high metal cost. [36][37][38] Both Fliedel et al 40 and McKeown et al 41 have reported systems based on Zn(II)-complexes, with the latter achieving up to 100% Me-LA conversion within 1 h at 90°C. Interestingly, McKeown et al 42 recently demonstrated shifting to an analogous propylenediamine system afforded superior activity, achieving 81% conversion within 30 minutes at 50°C, highlighting the influence of metal-ligand relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Cantat [ 66 ] and his group have depolymerized polycarbonates, polyesters, and polyethers using hydrosilanes as reductants and metal-free catalysts to generate functional chemicals such as alcohols and phenols at room temperature. They also reported the depolymerization of polyesters (such as polylactic acid, or PLA) in the presence of hydrosilanes with the cationic pincer complex as catalyst toward the formation of silyl ethers or the corresponding alkanes under mild conditions [ 67 ]. Liu et al [ 68 ] reported a series of imidazole-anion-derived ionic liquid were facilely synthesized and used for efficient catalyzing alcoholysis of polyester wastes, such as PLA and polyhydroxybutyrate (PHB).…”
Section: Polymer Depolymerization Methodsmentioning
confidence: 99%